Predictors of clozapine concentration and psychiatric symptoms in patients with schizophrenia - Sang-In Park; Seoyoung Kim; Kwanwoo Park; Uijeong Yu; Yunjeong Jang; Bo-Hyung Kim; Ji Hyun Lee; Euitae Kim (PLoS ONE, 2025)
Clozapine has superior efficacy to other antipsychotics, especially in patients with treatment-resistant schizophrenia. However, its pharmacokinetics and pharmacodynamics vary largely among patients. We aimed to evaluate the clinical and genetic factors associated with the pharmacokinetics and pharmacodynamics of clozapine in patients with schizophrenia. Blood samples for clozapine pharmacokinetic assessment were collected from patients with schizophrenia at weeks 2 (visit 2), 8 (visit 3), and 18 (visit 4) from the initiation of clozapine treatment. The Positive and Negative Syndrome Scale (PANSS) score was assessed at baseline (visit 1) and visits 3 and 4. Linear mixed models were used to identify the clinical and genetic variables associated with the clozapine concentration and total PANSS score. A total of 45 patients were included in the pharmacogenomic analysis. Owing to the small sample size, we categorized concomitant medications into four groups. However, individual drugs may have different effects on clozapine concentration. Clozapine concentration was significantly associated with smoking status and cumulative clozapine dose. Clozapine concentration was significantly associated with five single nucleotide polymorphisms (SNPs) in three genes (rs28371726 and rs202102799 in CYP2D6, rs4148323 and rs34946978 in UGT1A1, and rs2011404 in UGT1A4). Furthermore, follow-up time, body mass index, and total bilirubin levels were significantly associated with the total PANSS scores. The PANSS score was significantly associated with four SNPs in two genes (rs7787082 and rs10248420 in ABCB1 and rs2133251840 and rs762502 in DRD4). This study suggests potential clinical and genetic predictors of clozapine concentration and psychiatric symptoms in patients with schizophrenia treated with clozapine. With further investigations in diverse populations, our findings may provide important information on variables to be considered in individualized clozapine treatment.